Decomposing socioeconomic inequality in the dietary diversity practice among children aged 6–23 months in Ethiopia - Lemlem Daniel Baffa; Berhanu Mengistu; Fikreab Desta (Scientific Reports)
Abstract Child malnutrition is a significant global burden, leaving millions of children malnourished. To mitigate this huge burden, child dietary diversity is used as one of the major interventions applied in the first two years of life. The adequate child dietary diversity in Ethiopia is only 8%, and the socioeconomic inequalities contributing to this low proportion are not well discovered. Therefore, this study aimed to assess the socioeconomic inequality in dietary diversity practice among children aged 6–23 months in Ethiopia. Secondary data obtained from the recent Ethiopian Mini Demographic Health Survey 2019 dataset was used. A total of 1610 weighted samples of children aged 6–23 months were included in the study. A two-stage stratified sampling technique was employed to select the study participants. STATA version 17.0 was used for coding and analysis. Erreygers normalized concentration index and concentration curve were used to assess the socioeconomic inequality in the dietary diversity practice of the children. Decomposition analysis was applied to identify factors contributing to socio-economic inequality. A P-value < 0.05 was used to declare the statistical significance of the factors. The Erreygers normalized concentration index was found to be 0.1005 with a standard error of 0.033 and a statistically significant p-value (p-value = 0.0026) and the concentration curve lay below the line of equality, showing that adequate dietary diversity practice is disproportionately concentrated among children from households with high socioeconomic status. The decomposition analysis showed that household wealth status (72.8%), educational status of the mother (20.6%), postnatal care (2.2%) were the statistically significant contributors to the pro-rich socioeconomic inequality of dietary diversity practice among the children. This study showed that there is a pro-rich socioeconomic inequality in dietary diversity practice among children aged 6–23 months in Ethiopia. Household wealth status, educational status of the mother, and postnatal care were identified as contributors to the occurrence of the inequality. Therefore, encouraging mothers to attend school and engaging households in income-generating activities is crucial to narrowing the inequality.